2013
DOI: 10.1152/advan.00078.2011
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and resources for teaching the mathematical modeling of athletic training and performance

Abstract: A number of professions rely on exercise prescription to improve health or athletic performance, including coaching, fitness/personal training, rehabilitation, and exercise physiology. It is therefore advisable that the professionals involved learn the various tools available for designing effective training programs. Mathematical modeling of athletic training and performance, which we henceforth call "performance modeling," is one such tool. Two models, the critical power (CP) model and the Banister impulse-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 97 publications
2
60
0
Order By: Relevance
“…Attempts have been made over the past 4 decades to describe training adaptations and predict competition performance by means of mathematical models that rely on training quantification and performance outcomes. 17,35,36,49,50 Nevertheless, no single physiological marker has been identified that can accurately quantify the fitness and fatigue responses to training or predict competition performance. This implies that sport scientists probably need to direct their efforts toward the measurement of markers that reflect an athlete's global capacity to respond or adapt to training.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made over the past 4 decades to describe training adaptations and predict competition performance by means of mathematical models that rely on training quantification and performance outcomes. 17,35,36,49,50 Nevertheless, no single physiological marker has been identified that can accurately quantify the fitness and fatigue responses to training or predict competition performance. This implies that sport scientists probably need to direct their efforts toward the measurement of markers that reflect an athlete's global capacity to respond or adapt to training.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Clarke and Skiba [1] argue that there remains a "dearth of longitudinal studies to guide long-term training program designs." There remain many challenges in integrating diverse sensor data, as well as challenges related to what to do with the information derived from these data.…”
Section: Introduction à Physical Activity Monitoring Capabilitiesmentioning
confidence: 99%
“…Conceptually, this constraint ensures that a longer period of training sufficiently prepares an individual for more intense short-term training effects. CTL can be calculated as (8) where the chronic training load C n and the daily training stress σ n on the n th day were used along with the time constant τ = 42 days to determine the chronic training load C n + 1 on day n + 1.…”
Section: )mentioning
confidence: 99%
“…The model accounted for two primary physiological components: the positive effects of training, called fitness, and the negative effects of training, called fatigue. Several studies have built upon the Banister model with promising results [5,6,8,10,12,15]. However, these studies also recognized that the Banister model was based on linear systems theory, which limits its accuracy and applicability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation